The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.2460/ajvr.2005.66.1729
|View full text |Cite
|
Sign up to set email alerts
|

Effects of osteogenic inducers on cultures of canine mesenchymal stem cells

Abstract: BMP-2 was capable of inducing markers of osteogenesis in short-term cultures of canine MSCs. In MSCs obtained from skeletally immature dogs, ascorbate was required for maximal effects of BMP These results define optimal conditions for stem cell osteogenesis in dogs and will facilitate development of stem cell-based treatments for dogs with fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 73 publications
5
45
0
1
Order By: Relevance
“…OSTEOPONTIN, also known as bone sialoprotein 1, is expressed in other tissues but is considered an osteoblast-specific marker. 28,51 Osteogenic differentiation and expression of osteogenic transcription factors have not been previously reported for canine MMSCs and PMSCs.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…OSTEOPONTIN, also known as bone sialoprotein 1, is expressed in other tissues but is considered an osteoblast-specific marker. 28,51 Osteogenic differentiation and expression of osteogenic transcription factors have not been previously reported for canine MMSCs and PMSCs.…”
Section: Discussionmentioning
confidence: 89%
“…This was supported by the morphological appearance of nodular aggregates that stained positively with Alizarin red and Von Kossa 20,28,35,50 and the mRNA expression of osteoblast markers. 26,28,51 Alkaline phosphatase, RUNX2, OS-TERIX, and OSTEOPONTIN expression was found in all osteoinduced MSCs. Basal expression of these markers was not detected in MSCs treated with standard culture medium, confirming differentiation down the osteogenic lineage.…”
Section: Discussionmentioning
confidence: 98%
“…Cultured mononucleated cells were characterized by fluorescence-assisted cell sorting (FACS) analysis based on previous reports [13,29,37]. For immunophenotypic analysis, third-passage canine MSCs were stained under ice conditions, according to the manufacturer's recommendations regarding the monoclonal antibodies (anti-CD9, anti-CD34, anti-CD44, and anti-CD45; Serotec, USA).…”
Section: Msc Isolation and Characterization From Canine Bone Marrowmentioning
confidence: 99%
“…MSCs are nonhematopoietic progenitor cells that are initially present in bone marrow [7,19,29,37]. Bone marrow-derived MSCs are also known as bone marrow stromal cells and are capable of in vitro differentiation into marrow and non-marrow cell types, such as adipocytes, chondrocytes, osteocytes, myocytes, and neurons [13,17,19,33,37]. A recent study has shown that canine bone marrow-derived MSC can form neurosphere-like clumps and differentiate into neuron-like cells expressing neuronal markers [19,37].…”
Section: Introductionmentioning
confidence: 99%
“…Veterinary clinical applications also afford an important animal-to-human translation opportunity, especially the pathology of clinical spinal cord injury (SCI) in dogs appears very similar to that documented in humans, as well as in cats and numerous examples of experimental SCI (Smith and Jeffery, 2006). Previous studies (Kadiyala et al 1997;Bruder et al 1998;Arinzeh et al 2003;Volk et al 2005) of canine BMSCs have focused on their osteogenic properties because of the wide clinical applicability. The osteogenic property of canine BMSCs has also been exploited in the field of tissue engineering, particularly in an attempt to promote periodontal tissue regeneration (Hasegawa et al 2006).…”
mentioning
confidence: 95%